2005
DOI: 10.1080/10473289.2005.10464611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trickle-Bed Air Biofilter Performance under Periodic Stressed Operating Conditions as a Function of Styrene Loading

Abstract: Trickle-bed air biofilters (TBABs) are suitable for treating volatile organic compounds (VOCs) at a significantly high practical loading because of their controlled environmental conditions. The application of TBAB for treating styrene-contaminated air under periodic backwashing and cyclical nonuse periods at a styrene loading of 0.64 -3.17 kg chemical oxygen demand (COD)/m 3 ⅐day was the main focus of this study. Consistent long-term efficient performance of TBAB strongly depended on biomass control. A period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Recent studies [24,25] have demonstrated that when the loading rate of a mixture of hydrophobic and hydrophilic compounds is below a saturation of the catabolic capacity of the mixed culture, both types of the components can reach a RE above 98%. The variations of the RE that manifested themselves at the high loading rates (Figures 3c and 5b-5d) agree with those of Kim et al [5] for toluene, styrene, and MIBK high loadings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies [24,25] have demonstrated that when the loading rate of a mixture of hydrophobic and hydrophilic compounds is below a saturation of the catabolic capacity of the mixed culture, both types of the components can reach a RE above 98%. The variations of the RE that manifested themselves at the high loading rates (Figures 3c and 5b-5d) agree with those of Kim et al [5] for toluene, styrene, and MIBK high loadings.…”
Section: Discussionsupporting
confidence: 89%
“…Paint solvents are particularly prevalent air pollutants and consist of a mixture of VOCs containing both hydrophobic and hydrophilic components. Their removal from waste air has recently been studied using biotrickling filters [2][3][4][5] and biofilters [6,7]. These studies have demonstrated the general efficacy of biological systems in treating paint solvent emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid n-hexane was injected via a syringe pump and vaporized into the air stream. Buffered nutrient solution was supplied at a rate of 2.0 L day À1 ; the composition of the nutrient solution is similar to that reported by Kim et al (2005c). The experimental runs for the four biofilters were conducted in four phases (I-IV).…”
Section: Trickling Biofiltersmentioning
confidence: 94%
“…The detection limit was 0.001% v CO 2 . A detailed description of the analytical method was provided previously by Cai et al (2005) and Kim et al (2005c).…”
Section: Methodsmentioning
confidence: 99%
“…The number of studies simulating industrial emissions has increased, aimed at proving the viability or adjusting the operating conditions of the technologies at an industrial scale. These experiments have involved treating mixtures of compounds [11], applying starving periods [12,13] or using transient conditions with or without activated carbon prefilters coupled to the bioreactor in order to operate the system under more stable conditions [14,15]. However, the technology must progress further before its use at an industrial scale, with few studies in the literature on pilot or industrial prototypes [16][17][18][19], and to facilitate this scale-up it is necessary to keep studying the process at the laboratory scale.…”
Section: Introductionmentioning
confidence: 97%